Development of a system of risk management in the enterprises of the Republic of Kazakhstan and efficiency of using of the foreign experience (Journal of Economic Research & Business Administration, 2015)
Risk management is an integral part and plays a crucial important role in successful execution of strategic objectives of any enterprise. The system of a risk management begins with definition and an assessment of all difficulties of the enterprise`s activity. In a consequence it is considered alternative, that is ways with low risk and high profit. Practice of risk management which is widespread abroad, slowly came and to our country. Applying foreign experience the Kazakhstan companies organize policy of risk management in own divisions. But it is not a lot. Generally, it`s the national, large companies and financial organizations For example, JSC “Kazakhtelekom”, JSC “NAK Kazatomprom”, JSC “Kaztransgaz” and banks. Certainly, introduction of this system will help to prevent many risks. Therefore using of a risk management very important for many Kazakhstan companies.
Keywords: risk; admin; system; assessment; risk-management; enterprise